2022
DOI: 10.1002/app.52226
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new bifunctional molecule based on castor oil and CO2 useful for polyurethanes

Abstract: A new bifunctional biobased molecule, the carbonated methyl ester of ricinoleic acid maleate (CME‐RAM), useful for polyurethanes, was obtained from castor oil and CO2. This molecule bears carbonate and maleate functionalities that can participate, respectively, in aza‐Michael and aminolysis reactions. Maleate moieties are strong Michael acceptors and they were introduced into the fatty molecule using mild conditions. The synthetic steps include maleinization of castor oil followed by the simultaneous esterific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…However, the swelling is higher in Amberlite IR‐120 due to lower content of divinylbenzene (DVB) (8%) in comparison with Amberlyst 15 (20% DVB). In comparison with other studies with vegetable oils, a longer reaction time was required for the epoxidation of UA triglyceride under similar reaction conditions 15,28–32 . These differences in the reactivity of the internal and terminal double bonds have been observed by other authors and they have been justified based on the inductive effects of the alkyl groups.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…However, the swelling is higher in Amberlite IR‐120 due to lower content of divinylbenzene (DVB) (8%) in comparison with Amberlyst 15 (20% DVB). In comparison with other studies with vegetable oils, a longer reaction time was required for the epoxidation of UA triglyceride under similar reaction conditions 15,28–32 . These differences in the reactivity of the internal and terminal double bonds have been observed by other authors and they have been justified based on the inductive effects of the alkyl groups.…”
Section: Resultssupporting
confidence: 52%
“…In comparison with other studies with vegetable oils, a longer reaction time was required for the epoxidation of UA triglyceride under similar reaction conditions. 15,[28][29][30][31][32] These differences in the reactivity of the internal and terminal double bonds have been observed by other authors and they have been justified based on the inductive effects of the alkyl groups. That is, the terminal double bonds have a less electrophilic character in relation to the internal double bonds, which decreases the epoxidation rate.…”
Section: Epoxidation Reactionmentioning
confidence: 56%
See 1 more Smart Citation
“…In view of the drive toward sustainable and green materials, there is substantial and increasing interest in exploring renewable NIPU and NIPTU materials as replacements for petroleum-based PU and PU-like materials. Numerous studies have reported on biobased PHUs synthesized or capable of being synthesized from unsaturated raw materials like epoxidized soybean oil, 37,60,61 epoxidized castor oil, 62,63 or other renewable materials like limonene, 64 lignin, 65 and furfural. 66 However, reports on biobased NIPTUs are extremely rare; we have found only one study reporting on a biobased NIPTU, which was derived from eugenol or clove oil, 49 a compound that is widely used in the food industry.…”
Section: ■ Introductionmentioning
confidence: 99%